The birth of tragedy - Nietzsche, Friedrich Wilhelm, 1844-1900 (Oxford University Press, 2000)
"In [this 1872 book] Nietzsche explores the origin of Greek tragedy and its relevance to the German culture of his time. For Nietzsche, Greek tragedy is the expression of a culture that has achieved a balance between Dionysian insight intoi the chaos and suffering which underlies all existence, and the discipline and clarity of rational Apollonian form. In order to promote a return to these values which modern societies have lost, Nietzsche attacks the complacent rationalism of late nineteenth century German culture and makes an impassioned plea for the regenerative potential of the music of Wagner. In its wide-ranging discussion of the nature of art, science, and religion, his argument raises important questions about thye problematic nature of cultural origins which still concern us today."-- Provided by publisher.
Keywords: Greek drama (Tragedy) -- History and criticism.; Tragedy.; Ethics.; Music -- Philosophy and aesthetics.; Aesthetics.; Psychiatry; Ethics; Tragédie grecque -- Histoire et critique.; Tragédie.; Morale.; Musique -- Philosophie et esthétique.; tragedies.; ethics (philosophy); tragedy (general genre); PHILOSOPHY -- Aesthetics.; Aesthetics; Greek drama (Tragedy); Music -- Philosophy and aesthetics; Tragedy; Die Geburt der Tragödie aus dem Geiste der Musik (Nietzsche); Criticism, interpretation, etc.